2004
DOI: 10.1097/00006982-200410000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Surgery With and Without Internal Limiting Membrane Peeling for Macular Hole Repair

Abstract: Internal limiting membrane peeling shows high closure and low reopening rates in macular hole surgery. ILM peeling is beneficial in older holes but is limited in larger holes. ILM peeling does not significantly improve visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 27 publications
2
62
0
8
Order By: Relevance
“…These include stage of the hole, hole duration, hole size, preoperative visual acuity, and whether or not peeling of the ILM is performed. [7][8][9][10] Various studies have confirmed that shorter hole duration and lower stage of macular hole, together with ILM peeling at the time of surgery are associated with a higher anatomical closure rate. 8,9 However, the role of posturing in macular hole surgery remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include stage of the hole, hole duration, hole size, preoperative visual acuity, and whether or not peeling of the ILM is performed. [7][8][9][10] Various studies have confirmed that shorter hole duration and lower stage of macular hole, together with ILM peeling at the time of surgery are associated with a higher anatomical closure rate. 8,9 However, the role of posturing in macular hole surgery remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Various studies have confirmed that shorter hole duration and lower stage of macular hole, together with ILM peeling at the time of surgery are associated with a higher anatomical closure rate. 8,9 However, the role of posturing in macular hole surgery remains controversial. A study designed to objectively evaluate the time of post-operative posturing by patients undergoing macular hole surgery questioned the importance of posturing in determining the success of macular hole surgery.…”
Section: Discussionmentioning
confidence: 99%
“…24 Notwithstanding, the exact mechanism underlying the success remains equivocal. Some investigators argue that it is because of a reduction in vitreoretinal tangential traction; 23 others support the notion that glial proliferation is stimulated, resulting in an increased macular hole closure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports also indicated that experienced surgeons could achieve an anatomical closure rate of more than 90% after ILM peeling for macular holes. [2][3][4][5] Although there are other dyes with greater safety, including trypan blue and brilliant blue G, ICG still remains the standard for staining transparent ILM by some surgeons in some countries due to its greater availability and its optimal, selective staining of ILM. However, the potential adverse effects of ICG on retinal tissues remain a concern.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Internal limiting membrane (ILM) removal can further relieve foveal traction from within the retinal surface and provide good anatomical and functional results with high closure and low reopening rates. 4,5 Staining ILM with a dye can facilitate visualization of the ILM during surgery and help complete removal. Among different dyes, indocyanine green (ICG) was first used for ILM staining and remained the standard in some countries because the staining of ILM and the ease of ILM removal were optimum with ICG.…”
Section: Introductionmentioning
confidence: 99%